Heavy Metals in Selected Medicinal Plants Originated in Dana Biosphere Reserve, Jordan - Mohammad Sanad Abu-Darwish (International Journal of Phytomedicine, 2014)
Heavy Metals in Selected Medicinal Plants Originated in Dana Biosphere Reserve, Jordan